MODELO MATEMáTICO DE LA GESTIóN DE LA ESTRATEGIA - Murillo C., Saulo (2019)
This work shows recent theoretical contributions in the area of competition and strategy which have been expressed by a mathematical model. Taking as its starting point the theory of decision making, so that may be used for empirical research. The development objective of the model is to explain the possible outcomes of the strategic management of a firm, having as theoretical base the theory of competition and strategy. Finally, using the model it is concluded that competitive advantage is not exploitable feature, but is the result of the deployment of skills that are imperative for the best performance and business, understanding the latter as the supply of attributes of customer value. In this sense, competitive advantage is a condition with extrinsic in relation to other competitors. Furthermore, it is considered that the quality that enables a company to get better returns is the distinctive competence, whose value is evaluated in the operation of the company.